2008
DOI: 10.3904/kjim.2008.23.3.121
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-modified albumin (IMA) is not useful for detecting myocardial ischemia during symptom-limited exercise stress tests

Abstract: Background/Aims: We examined the ischemia-modified albumin (IMA) level during exercise in patients with coronary artery disease (CAD).Methods: Forty patients with a history of chest pain underwent both symptom-limited treadmill exercise stress testing and coronary angiography within one week. During the treadmill tests, blood samples were obtained at baseline and 5 min after exercise to measure the serum IMA level.Results: Of the 40 patients, fourteen (35%, CAD group) had significant coronary artery stenosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(24 reference statements)
1
2
1
Order By: Relevance
“…This finding is in contrast with the majority of data in the literature (26, 27, 28, 29). However, there are also studies in which no significant difference was found for IMA in similarly arranged groups, which is in parallel with our results (30, 31). We believe that these differences may suggest that IMA levels could vary with factors such as, the duration of the effort test, the amount of vascular occlusion and the severity of coronary artery disease.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in contrast with the majority of data in the literature (26, 27, 28, 29). However, there are also studies in which no significant difference was found for IMA in similarly arranged groups, which is in parallel with our results (30, 31). We believe that these differences may suggest that IMA levels could vary with factors such as, the duration of the effort test, the amount of vascular occlusion and the severity of coronary artery disease.…”
Section: Discussionsupporting
confidence: 92%
“…However, the area under curve of ROC curve of IMA was not good enough and might not be a good candidate for diagnosis of myocardial infarction. The lack of diagnostic potential of IMA was also mentioned in many studies [1,21,22]. However, our results showed that combinatorial determination of these two biomarkers gave not good enough for NSTEMI diagnosis as it, although it slightly increased NPV and test efficiency.…”
Section: Discussioncontrasting
confidence: 71%
“…Although the mechanism of the formation of ischaemia‐modified albumin (IMA) is not fully understood, it is postulated that IMA is produced as a result of a change in the N‐terminal structure of albumin as a result of a series of biochemical reactions triggered by oxygen deficiency (Kim et al, ). Serum IMA levels have been a useful biomarker for monitoring ischaemic and infectious events, type 2 diabetes mellitus, chronic hepatitis C and pulmonary embolism.…”
Section: Introductionmentioning
confidence: 99%